2015
DOI: 10.1021/acscombsci.5b00063
|View full text |Cite
|
Sign up to set email alerts
|

Price-Focused Analysis of Commercially Available Building Blocks for Combinatorial Library Synthesis

Abstract: Combinatorial libraries are synthesized by combining smaller reagents (building blocks), the price of which is an important component of the total costs associated with the synthetic exercise. A significant portion of commercially available reagents are too expensive for large scale work. In this study, 13 commonly used reagent classes in combinatorial library synthesis (primary and secondary amines, carboxylic acids, alcohols, ketones, aldehydes, boronic acids, acyl halides, sulfonyl chlorides, isocyanates, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 15 publications
1
68
0
Order By: Relevance
“…Novelty and commercial accessibility are yet other factors that are considered to be very important. [229,230] Analysis of the reagent classes that are most popularw ith medicinal chemists reflectsr esults obtainedf rom studies on the most frequently used reactions. In particular, amines (especially secondary amines), carboxylic acids, and boronic acids or their derivativesw ere ranked most highlyo nd esirability;f ollowed by arylation and alkylation agents;a ldehydes,a lcohols, and aromatic amines;a nd, finally,s ulfonyl halides, ketones, and isocyanates.…”
Section: Building Blocks For Drug Discoverymentioning
confidence: 99%
“…Novelty and commercial accessibility are yet other factors that are considered to be very important. [229,230] Analysis of the reagent classes that are most popularw ith medicinal chemists reflectsr esults obtainedf rom studies on the most frequently used reactions. In particular, amines (especially secondary amines), carboxylic acids, and boronic acids or their derivativesw ere ranked most highlyo nd esirability;f ollowed by arylation and alkylation agents;a ldehydes,a lcohols, and aromatic amines;a nd, finally,s ulfonyl halides, ketones, and isocyanates.…”
Section: Building Blocks For Drug Discoverymentioning
confidence: 99%
“…Replacement of the azide with a primary amine nucleophile, the most common commercially available nitrogen containing substrate, is of great interest to the synthetic community. [9] In 1986, Sakai et al reported the synthesis of substituted 1,2,3-triazoles 11 through the reaction of an a,a-dichloroketone 10, tosylhydrazide and a primary amine (Figure 1 b). [10] The scope of this transformation was explored by Westermann and co-workers [11] and demonstrated on scale by Hanselmann et al, [12] providing a novel process to form this heterocyclic core.…”
mentioning
confidence: 99%
“…With more than four thousand commercially available aryl boronic acids,t hey have become one of the most versatile building blocks in organic synthesis. [1] Notably,recent significant advances in borylation methods has made aryl boronic acids,particularly those that are heavily functionalized, more readily accessible. [2] Theunique reactivity of substances in this family has led to am yriad of carbon-carbon and carbonheteroatom bond-forming processes,which are either difficult to carry out or show poor functional-group tolerance,and/or low efficiencywhen their halide counterparts are employed as substrates.These reactions,which include the introduction of oxygen, [3] nitrogen, [4] and halogen, [5] as well as alkyl, alkynyl, alkenyl, and alkyl moieties, [6] are generally accomplished using transition-metal complexes (Scheme 1a).…”
mentioning
confidence: 99%